427 The role of virtual visits in cardiology: from the pandemic era to future perspectives. (8th December 2021) - Mei, Mariachiara; Di Iorio, Martina; Bernardini, Alessia; Magnocavallo, Michele; Vetta, Giampaolo; Piro, Agostino; Giunta, Giuseppe; Quaglione, Raffaele; Chimenti, Cristina; Trivigno, Sara; Mitacchione, Gianfranco; Fedele, Francesco; et al.
Abstract: Aims: During the Coronavirus Disease 2019 (COVID-19) pandemic in-person visits were reduced to prevent potential risk of exposure. Virtual visits (VVs) represent an innovative model to take care of patients with cardiac implantable electronic devices (CIEDs). The aim of this study is to evaluate the safety and feasibility of VV in the management of CIED patients. Methods and results: We performed a prospective study including all CIED patients who received a VV from July 2020 to July 2021. Blood pressure, arterial oxygen saturation, heart rate, and body weight were registered by the patient. Moreover, we sent to the patient a questionnaire to evaluate the patients' satisfaction about VV. We enrolled 182 patients in the study period. The mean age of patients was 70.2 ± 13.5 years-old and the majority (61.1%) was male. In two cases, VVs were not performed due to technical issues. Overall, 70.9% of patients utilized a smartphone, while 20.1% and 9% used, respectively, a tablet or a personal computer. The mean duration of VV was 27.8 ± 7.8 min. Patients helped by a caregiver were 64 (35.2%). One urgent/emergent in‐person visit was performed in a patient with acute heart failure. Overall, VV was preferred to in-person evaluation. Conclusion: VV is a safe and feasible approach to follow-up CIED patients. A high degree of patient satisfaction was reached after VV. The use of VV has promising potential and should be implemented beyond COVID-19 period and integrated in the healthcare system as a new model of care.